An Analysis Clitics in the Novel Allegiant by Veronica Roth - Slamet Utomo; Lina Karuniawati (Jurnal Prakarsa Paedagogia, 2019)
This study aims to find out the type and the function of English clitics, which mostly are used in informal language. The researcher analyzes English clitic in Chapter II (Tobias) of Allegiant Novel by Veronica Roth. The researcher found 47 clitics. There were two types of clitics consist of (1) one is proclitic and (2) 46 are enclitics. Furthermore, also have three functions of clitics with (1) six variants encompassed (..’d, ..’m, ..’s, ..’re, ..’ve, ..’ll) consist of 27 enclitics as verbal functions, (2) 15 enclitics as adverbial function (n’t), and (3) as pronominal function has five clitics with two variants encompassed (o’.., genitive (‘s)) which consist of four enclitics and one proclitic.